Confinement synthesis in porous molecule-based materials: a new opportunity for ultrafine nanostructures. Issue 6 (19th January 2022) - Cao, Li-Ming; Zhang, Jia; Zhang, Xue-Feng; He, Chun-Ting
Abstract : The space-, coordination-, and/or ion-confinement in porous molecule-based materials (PMMs) endow the PMM-confinement (pyrolysis) synthesis to construct a variety of ultrafine nanostructures. Abstract : A balance between activity and stability is greatly challenging in designing efficient metal nanoparticles (MNPs) for heterogeneous catalysis. Generally, reducing the size of MNPs to the atomic scale can provide high atom utilization, abundant active sites, and special electronic/band structures, for vastly enhancing their catalytic activity. Nevertheless, due to the dramatically increased surface free energy, such ultrafine nanostructures often suffer from severe aggregation and/or structural degradation during synthesis and catalysis, greatly weakening their reactivities, selectivities and stabilities. Porous molecule-based materials (PMMs), mainly including metal–organic frameworks (MOFs), covalent organic frameworks (COFs) and porous organic polymers (POPs) or cages (POCs), exhibit high specific surface areas, high porosity, and tunable molecular confined space, being promising carriers or precursors to construct ultrafine nanostructures. The confinement effects of their nano/sub-nanopores or specific binding sites can not only effectively limit the agglomeration and growth of MNPs during reduction or pyrolysis processes, but also stabilize the resultant ultrafine nanostructures and modulate their electronic structures and stereochemistry in catalysis. In this review, we highlight the latest advancements in the confinement synthesis in PMMs for constructing atomic-scale nanostructures, such as ultrafine MNPs, nanoclusters, and single atoms. Firstly, we illustrated the typical confinement methods for synthesis. Secondly, we discussed different confinement strategies, including PMM-confinement strategy and PMM-confinement pyrolysis strategy, for synthesizing ultrafine nanostructures. Finally, we put forward the challenges and new opportunities for further applications of confinement synthesis in PMMs.